Antibiotic Resistance Pattern of Shigella spp. Among Gastroenteritis Patients at Tertiary Care Hospital in Pokhara, Nepal - Thapa, Kabi; Bhattachan, Balkrishna; Gurung, Raja Ram; Katuwal, Archana; Khadka, Jagat Bahadur (Nepal Journal of Biotechnology, 2017)
Shigellosis, a disease caused by Shigella species. It is a major public health problem in developing nations like Nepal, where communities having poverty; poor sanitation, personal hygiene, and water supplies. The main aim of our study is to isolate and identify Shigella spp. from gastroenteritis patients and to find out its drug resistance pattern. A cross-sectional study was carried out based on routinely attending outpatients and inpatients. A total of 225 stool samples collected from gastroenteritis patients were processed from 20 April to 24 September 2014 in Western Regional Hospital, Pokhara, Nepal. Standard microbiological procedures were followed for the isolation of Shigella spp. After that slide agglutination kit method was used for identification of Shigella spp. Finally, Kirby-Bauer disc diffusion method was done for an antimicrobial resistance test. Of the total 225 gastroenteritis patients, 133 were detected as bacterial positive cases. Among positive cases, Shigella spp. was identified in 10.5%. Age wise, an infection rate of Shigella in patients <15-years old was found higher i.e. 7.3% than in patients ≥ 15 years old i.e. 4.5% with the (p = 0.432) at 95% CI. The infection rate of S. dysenteriae, S. flexneri, and S. sonnei was detected in 28.6%, 57.1%, and 14.3% respectively. For the antimicrobial test, eight types of antibiotics were used. The most resistance pattern of isolated Shigella spp. was found in nalidixic acid, and co-trimoxazole 92.8% followed by ampicillin 64.3% and ciprofloxacin 42.8% etc. Our study reported that endemicity of Shigellosis with S. flexneri is the predominant group in gastroenteritis patients. This finding suggests that co-trimoxazole, nalidixic acid, ciprofloxacin and ampicillin should not be used experimentally as first-line drugs for shigellosis treatment.